THIN-LAYER CHROMATOGRAPHY AND IMAGE ANALYSIS FOR QUANTITATION - PHATTANAWASIN, PANADDA; SOTANAPHUN, UTHAI; SRIPHONG, LAWAN; BURANA-OSOT, JANKANA; AKKARAWARANTHORN, JARIYA; NANTANAKORN, ARUNYA (Thai Bulletin of Pharmaceutical Sciences, 2018)
การใช้วิธีโครมาโทกราฟีแบบชั้นบาง (thin-layer chromatography, TLC) ร่วมกับเทคนิคการวิเคราะห์เชิงภาพได้นำมาประยุกต์ใช้สำหรับการหาปริมาณสารสำคัญโดยเฉพาะในตัวอย่างประเภทสมุนไพรและผลิตภัณฑ์ธรรมชาติ ขั้นตอนโดยรวมของวิธีประกอบด้วย การแยกสารที่ต้องการวิเคราะห์หาปริมาณออกจากสารอื่นและตรวจพบได้อย่างชัดเจนบนแผ่น TLC การบันทึกและเก็บข้อมูลภาพของแผ่น TLC ด้วยเครื่องสแกนเนอร์หรือกล้องดิจิทัล การวิเคราะห์ภาพ TLC เพื่อหาความสัมพันธ์ระหว่างความเข้มสีกับปริมาณสารแต่ละจุดด้วยโปรแกรมคอมพิวเตอร์ที่เหมาะสม และการตรวจสอบความใช้ได้ของวิธี ข้อดีหลักของวิธีนี้คือ ความสะดวก ความรวดเร็ว การใช้อุปกรณ์และเครื่องมือที่จัดหาได้ง่ายในราคาไม่สูงมาก และหากมีการพัฒนาวิธีการอย่างเหมาะสมยังพบว่าผลการวิเคราะห์ที่ได้มีความถูกต้อง แม่นยำ และไม่แตกต่างจากผลการวิเคราะห์ด้วยเครื่องเดนสิโตมิเตอร์หรือเครื่องมือขั้นสูงประเภทอื่น ๆ The use of thin-layer chromatography (TLC) combined with image analysis is applied for the quantitation of active ingredient especially in herbal samples and natural products. The overall process of the technique includes the separation of the compound to be quantified and clearly detected on a TLC plate, an image record of the TLC plate with a scanner or a digital camera, TLC-image analysis for relative correlations between color intensity and quantity of a compound in each spot using suitable computer programs, and method validation. The advantages of this method are convenience, rapidness and the use of simple and low cost equipment. Also, if properly developed, the analytical results obtained from this method are shown to be accurate, precise and no different from the results determined using a densitometer or other advanced instrument.